A survey of quality-of-life tools used in the routine care of patients with multiple myeloma. (9th March 2023) - Kirkpatrick, Suriya; Campbell, Karen; Harding, Sam
Abstract : Background: New treatment options have significantly improved the life expectancy of myeloma patients such that their cause of death is increasingly likely to be from something other than myeloma. Furthermore, the adverse effects of short- or long-term treatments as well as the disease are impacting on quality of life (QoL) for longer periods of time. Understanding people's QoL and what is important to them, is part of providing holistic care. Although QoL data has been collected for many years in myeloma studies, they have not been used to inform patient outcomes. There is growing evidence that supports the assessment of 'fitness' and consideration of QoL as part of routine myeloma care. A national survey was carried out to discover which QoL tools are currently being used in the routine care of myeloma patients, by whom and at which time point. Methods: An online survey using SurveyMonkey was adopted for flexibility and accessibility. The link to the survey was circulated via Bloodwise, Myeloma UK and Cancer Research UK contact lists. Paper questionnaires were circulated at the UK Myeloma Forum. Results: Data about practices in 26 centres were collected. This included sites across England and Wales. Three out of 26 centres collect QoL data as part of standard care. QoL tools used include EORTC QLQ-My20/24, MyPOS, FACT-BMT and Quality of Life Index. Questionnaires were completed by patients before, during or after a clinic appointment. Clinical nurse specialists calculate the scores and create a care plan. Conclusion: Despite growing evidence to support an holistic approach to management of myeloma patients, there is a lack of evidence to confirm that health-related QoL is being addressed in standard care. This is an area that needs further research.